Long PCRs of Transposons in the Structural Analysis of Genes Encoding Acquired Glycopeptide Resistance in Enterococci. (March 1998) - Haaheim, H.; Dahl, K.H.; Simonsen, G.S.; Olsvik, Ø.; Sundsfjord, A.
Glycopeptide-resistant enterococci (GRE) associated with multiple antibiotic resistance present a major challenge to clinical practice and infection control due to limited or nonexistent antimicrobial treatment options. The genes encoding VanA- and VanB-type glycopeptide resistance have been shown to reside on transposons Tn 1546 and Tn 1547, respectively. These transferable genetic elements may carry the resistance determinants between and within different ecological niches. Molecular epidemiological studies of nosocomial outbreaks of VanA- and VanB-type GRE indicate horizontal transfer of glycopeptide resistance genes as an important mechanism for the spread of GRE. To target infection control and better understand the epidemiology of GRE, outbreak investigations and molecular epidemiological studies should therefore apply at least two different approaches, i.e., molecular-typing methods to analyze bacterial genomic heterogeneity and structural analysis of mobile resistance determinants. Here we describe the development and use of long PCRs in the structural analysis of van A and van B gene clusters in GRE.